Morphological and Whole-Word Semantic Processing Are Distinct: Event Related Potentials Evidence From Spoken Word Recognition in Chinese - Zou, Lijuan; Packard, Jerome L.; Xia, Zhichao; Liu, Youyi; Shu, Hua (Frontiers in Human Neuroscience, 2019)
Behavioral and imaging studies in alphabetic languages have shown that morphological processing is a discrete and independent element of lexical access. However, there is no explicit marking of morphological structure in Chinese complex words, such that the extent to which morpheme meaning is related to word meaning is unknown. Event-related potentials (ERPs) were used in the present study to investigate the dissociation of morphemic and whole-word meaning in an auditory-auditory primed lexical decision task. All the priming and target words are compounds consisting of two Chinese morphemes. The relationship between morpheme and whole-word meaning was manipulated while controlling the phonology and orthography of the first syllable in each prime-target pair. A clear dissociation was found between morphemic and whole-word meaning on N400 amplitude and topography. Specifically, sharing a morpheme produced a larger N400 in the anterior-central electrode sites, while sharing whole-word meaning produced a smaller N400 in central-posterior electrode sites. In addition, the morphological N400 effect was negatively correlated with the participants’ reading ability, with better readers needing less orthographic information to distinguish different morphemes in compound words. These findings indicate that morphological and whole-word meaning are dissociated in spoken Chinese compound word recognition, and that even in the spoken language modality, good readers are better able to access the meaning of individual morphemes in Chinese compound word processing.